An Improvement in ant Algorithm Method for Optimizing a Transport Route with Regard to Traffic Flow. (2017) - Danchuk, Viktor; Bakulich, Olena; Svatko, Vitaliy
Abstract: The modification of ant algorithm method for optimizing the transportation route with regard to traffic flow in the street network has been developed in this paper. It was also made possible to confirm the results of optimization of partly covered distance for calculating a further route when changing the length of links while ant agents traveling on the links of a two-way graph. Besides, the procedure of ant agents' traffic in the graph was improved so that ant agents can travel both synchronously and asynchronously. The proposed modification of ant algorithm for optimizing the goods delivery route when changing the speed of traffic flow in specific sections of the street network has been approbated, using the example of Kyiv's specific street network within traveling salesman problem. We conducted the quantitative and comparative analysis of solving the problem of optimization of the goods delivery route in the street network, applying ant algorithm method and the respective findings of other existing classical methods. The obtained results of the study show the prospects of applying the proposed modification of ant algorithm for solving routing problems, particularly for transport networks which are characterized by high dimensionality and dynamism of functional parameters.